2012
DOI: 10.1161/atvbaha.111.243733
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor Blocks Angiogenesis via Its Carboxyl Terminus

Abstract: Objective Tissue factor pathway inhibitor (TFPI) is the primary regulator of the tissue factor (TF) coagulation pathway. As such, TFPI may regulate the pro-angiogenic effects of TF. TFPI may also affect angiogenesis independently of TF, through sequences within its polybasic carboxyl terminus (TFPIct). We aimed to determine the effects of TFPI on angiogenesis and the role of TFPIct. Methods and results Transgenic overexpression of TFPI attenuated angiogenesis in the murine hind-limb ischemia model and an aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Oxidative stress and angiogenesis were also closely related to hypoxia, as described above [ 49 , 50 , 53 ]. Among these 32 genes, at least six genes, including ARNT (aryl hydrocarbon receptor nuclear translocator, hypoxia-inducible factor 1-beta), GADD45A (growth arrest and DNA-damage-inducible 45 alpha), IDH1 (isocitrate dehydrogenase 1 (NADP+)), NRP1 (neuropilin 1), ROMO1 (reactive oxygen species modulator 1) and TFPI (lipoprotein-associated coagulation inhibitor) could be regarded as important candidate genes for animal hypoxia adaptation since these genes were closely related to HIF-1, ROS, oxidative stress, angiogenesis and vascular repair [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. ARNT is a constituent subunit of HIF-1 and hypoxia can inhibit induction of aryl hydrocarbon receptor activity in an ARNT-dependent manner [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and angiogenesis were also closely related to hypoxia, as described above [ 49 , 50 , 53 ]. Among these 32 genes, at least six genes, including ARNT (aryl hydrocarbon receptor nuclear translocator, hypoxia-inducible factor 1-beta), GADD45A (growth arrest and DNA-damage-inducible 45 alpha), IDH1 (isocitrate dehydrogenase 1 (NADP+)), NRP1 (neuropilin 1), ROMO1 (reactive oxygen species modulator 1) and TFPI (lipoprotein-associated coagulation inhibitor) could be regarded as important candidate genes for animal hypoxia adaptation since these genes were closely related to HIF-1, ROS, oxidative stress, angiogenesis and vascular repair [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. ARNT is a constituent subunit of HIF-1 and hypoxia can inhibit induction of aryl hydrocarbon receptor activity in an ARNT-dependent manner [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…GADD45A was an important sensors of oxidative stress and could be induced by hypoxia [ 61 ], GADD45A knockdown could reduce oxidative stress by suppressing the p38 MAPK signaling pathway in CRL1730 human umbilical vein endothelial cells (HUVEC) [ 62 ]. TFPI played an inhibitory role on angiogenesis by regulating the proangiogenic effects of tissue factors or blocking VEGFR2 activation directly and decreasing endothelial cell migration through peptides within its carboxyl terminus [ 63 ]. Nrp1 is expressed in a variety of cells.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing evidence for non-hemostatic tumor-suppressive activities of TFPI. Studies of endothelial cell cultures have shown that recombinant TFPIα induces apoptosis [ 16 ], inhibits proliferation via the very low density lipoprotein receptor [ 17 ], and show anti-angiogenic and anti-migratory properties [ 18 , 19 ]. In addition, manipulation of their expression revealed that both the TFPIα and the TFPIβ isoform have tumor-suppressive features in breast cancer cells, similar to that observed in endothelial cells [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the in vitro observations, in vivo studies have demonstrated that both circulating recombinant TFPI and TFPI-expressing tumor cells significantly attenuated tumor growth [ 13 , 22 ] and lung metastasis in mice [ 13 , 23 ]. A transgenic murine model of TFPI overexpression suggested that the C-terminal end of TFPIα caused impaired angiogenesis by inhibition of phosphorylation of vascular endothelial growth factor receptor 2 [ 19 ]. A few TFPI and TF ( F3 ) single nucleotide polymorphisms (SNPs) have been reported and assigned a possible, but not definite role in modifying transcription or plasma levels of TFPI and TF [ 24 - 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of TFPIβ diminished TF-dependent CHO cell infiltration into lungs following tail vein injection into SCID mice and blocked consumptive coagulopathy induced in this model [31]. Over-expression of TFPIα through a smooth muscle cell promoter blocks vascular remodeling and angiogenesis in mice [33]. These in vivo anticoagulant effects of TFPI are potentially modified by a wide range of enzymes including metallo [34;35], neutrophil [36], fibrinolytic [37], and blood clotting proteases [38;39] that cleave at sites within the connecting regions between the Kunitz domains or at their active site.…”
Section: Inhibitory Activity Of Tfpiα and Tfpiβmentioning
confidence: 99%